Tinjauan Pustaka: Diagnosis Dan Tatalaksana Mastoidits - Nadhia Wihelga; RA Genta Syakira Hatta; Putu Ristyaning Ayu Sangging; Rani Himayani (JURNAL RISET RUMPUN ILMU KEDOKTERAN, 2023)
Mastoiditis is a disorder of the middle ear. Inflammation of the middle ear involves the mastoid cells of the temporal bone. Mastoiditis is generally a complication of otitis media. This is due to the connection between the middle ear and the mastoid air cells. This research method begins by searching articles on Google Scholar, PubMed and NCBI within the year range determined by the researcher and using the keywords Mastoiditis, Mastoiditis Diagnosis, Mastoiditis Management. The results of this study found that the diagnosis of mastoiditis can be made by history, physical examination and supporting examinations. Treatment that can be done in mastoiditis depends on the severity of the infection and its complications. administration of antibiotics, incision and drainage of mastoid abscess and mastoidectomy are the management of mastoiditis